SWOT Analysis on the Use of Haba Inggreh Android Application in High Schools in Nagan Raya Regency - Syahputri, Veni Nella; Ismail, Nyak Mutia; Kismullah; Darsan, Herri (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
Mobile application provides a spectrum of interactive and multimedia tools to improve the learning process. Unfortunately, this application not only brings benefits, but also portrays some flaws. Hence, this study aimed at finding out the strengths, weaknesses, opportunities, and threats that are potential from a newly-developed learning application named Haba Inggreh. This study belongs toqualitative deisgn, involving 29 students and 4 teachers from SMAN 1 Seunagan. Classroom observations and interviews were employed as the data collection techniques, and all the obtained data were analyzed using thematic analysis. The findings reveal that in terms of thestrength, both teachers and students agreed that the Haba Inggreh application enhances language acquisition. On the other hand, the weakness of this app is slow performance, which could frustrate the users, resulting in impeding effective learning. Furthermore, the opportunity of this app is that Haba Inggreh can be improved by raising interactivity and involvement. However, it also poses a threat, as using the app excessively for language learning is dangerous. Though Haba Inggreh offers helpful materials, language acquisition calls for real-world contact and immersion. Users could overuse the app and choose not to follow local wisdom.